Spin-coated YSZ thin films on silica substrate - Palisoc, Shirley Tiong (Animo Repository, 2012)
Different concentrations of yttria stabilized zirconia (YSZ) grown on silia (SiO2) substrate was investiaged in this paper. Suspension containing 10wt%, 30wt%, and 50wt% YSZ were fabricated using the spin coating technique on silica keeping all other parameters constant such as the coating parameters and sintering temperature. The surface morphology and thickness of the films were investigated using scanning electron microscopy (SEM). Results showed porous YSZ films w which become less porous as the concentration of YSZ increases. The thickness of the films was also affected by the YSZ concentration. As the concentration increases, the thickness of the films also increases. The crystal structure of the favricated films was also determined using X-Ray Diffraction (XRD) and Raman Spectroscopy. Both Techniques revealed a cubic fluorite structure independent of the concentration of YSZ.